Realizing the Constitutional Right to a Healthy Environment through the 3R Principle: Evidence from Passippo Landfill, Bone Regency - Latifah, Dini; Fahri, Marjana; Putri, Meilan Renisa; Rosita; Nurfazira (IAIN Bone, 2025)
Waste management remains a major environmental challenge in Bone Regency, South Sulawesi, directly affecting citizens’ constitutional right to a healthy environment. This study analyzes the implementation of the 3R (Reduce, Reuse, Recycle) principle within the local waste management system and its relation to the realization of constitutional environmental rights. Using a socio-legal (juridical-empirical) approach, it integrates normative analysis of the legal framework with empirical findings from field observations, interviews, and documentation at the Passippo Final Disposal Site (TPA) and the Palakka 3R Waste Processing Facility (TPST). The results reveal a significant gap between legal norms and practical implementation. While TPST Palakka applies the 3R principle through community-based sorting, composting, and recycling, TPA Passippo continues to rely on open dumping without processing. This disparity stems from weak institutional capacity, inadequate infrastructure, low public awareness, and limited interagency coordination. The study highlights the need to institutionalize the 3R principle through regulatory reform, capacity building, and participatory governance to ensure the fulfillment of constitutional environmental rights and promote ecological justice at the local level.